2012
DOI: 10.1002/art.34603
|View full text |Cite
|
Sign up to set email alerts
|

Digital acrometastasis revealing endometrial cancer relapse

Abstract: Clinical Images: Digital acrometastasis revealing endometrial cancer relapseThe patient, a 68-year-old woman with a history of localized endometrial adenocarcinoma who had undergone hysterectomy followed by sequential chemotherapy and radiation therapy, was referred for evaluation of a painful mass on the second finger of the right hand (left). The mass had been insufficiently controlled by nonsteroidal antiinflammatory drug treatment and had rapidly increased in size during the preceding month. The patient ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…From our search, there have only been two cases reported in the English literature 1 . Sur et al 2 reported a case of acrometastasis from the uterus which, however, was a uterine leiomyosarcoma and Ornetti et al 5 presented another case which was not reported formally.…”
Section: Discussionmentioning
confidence: 99%
“…From our search, there have only been two cases reported in the English literature 1 . Sur et al 2 reported a case of acrometastasis from the uterus which, however, was a uterine leiomyosarcoma and Ornetti et al 5 presented another case which was not reported formally.…”
Section: Discussionmentioning
confidence: 99%